The in vitro evaluation of synergistic effects of ciprofloxacin and berberine hydrochloride against Pseudomonas aeruginosa - Anis Zeraatpisheh; Melika Moradi; Maniya Arshadi; Behrouz Taheri; Massomeh Zahmatkeshan; Fereshteh Nezhad Dehbashi; Fariba Esmaeili; Bentolhoda Amanzadi; Zahra Farshadzadeh (BMC Microbiology)
Abstract Background Pseudomonas aeruginosa is a major cause of severe infections, leading to significant morbidity and mortality rates due to its ability of biofilm formation and antibiotic resistance. This study evaluates the in vitro antimicrobial and antibiofilm effects of ciprofloxacin and berberine hydrochloride, alone and in combination, against clinical and standard strains of P. aeruginosa. Methods Clinical isolates of carbapenem-susceptible P. aeruginosa (CSPA), carbapenem-resistant P. aeruginosa (CRPA), and the standard P. aeruginosa PAO1 strain were examined. Antimicrobial activity (MIC/MBC) and biofilm inhibition (MBIC/MBEC) were assessed using the microdilution method, checkerboard assay (FICI), and time-kill kinetics. Results The minimum inhibitory concentrations (MICs) of ciprofloxacin and berberine hydrochloride ranged from 0.5 to 64 µg/mL and 593 to 1187 µg/mL, respectively. The minimum bactericidal concentrations (MBCs) for both agents were ≥ 2× MIC. Neither ciprofloxacin nor berberine hydrochloride was able to eradicate 24-hour preformed biofilms (MBEC). However, biofilm prevention (MBIC) occurred at sub-MIC levels (0.5–1× MIC). The combination of ciprofloxacin and berberine hydrochloride demonstrated synergistic activity against PAO1 (FICI ≤ 0.5). The time-kill assay confirmed the bactericidal effect of this combination against PAO1 and CSPA isolates. Conclusion Berberine hydrochloride may serve as a promising synergistic agent to enhance the antimicrobial and antibiofilm activity of ciprofloxacin in vitro. This combination warrants further exploration as a therapeutic strategy against resistant infections.